Renal function in abdominal neuroblastoma patients undergoing proton radiotherapy. Issue 1 (21st September 2022) - Chevli, Neil; Grosshans, David R.; McAleer, Mary Frances; Foster, Jennifer H; Harrison, Douglas; McGovern, Susan L.; Paulino, Arnold C.
Abstract: Background: The purpose of this study is to analyze renal function outcomes in abdominal neuroblastoma patients undergoing proton therapy (PT). Procedure: From 2011 to 2019, two single‐institution Institutional Review Board‐approved protocols prospectively enrolled neuroblastoma patients for data collection. To assess renal function, serum creatinine (Cr), blood urea nitrogen (BUN), and creatinine clearance (CrCl) before proton therapy (pre‐PT) were compared with the values at last follow‐up. Results: A total of 30 children with abdominal neuroblastoma with median age 3.5 years (range, 0.9–9.1) at time of PT were included in this study. All patients underwent chemotherapy and resection of primary tumor prior to PT. Two patients required radical nephrectomy. Median follow‐up after PT was 35 months. Mean dose to ipsilateral and contralateral kidney was 13.9 and 5.4 Gy, respectively. No patients developed hypertension or renal dysfunction during follow‐up. There was no statistically significant change in serum BUN ( p  = .508), CrCl ( p  = .280), or eGFR ( p  = .246) between pre‐PT and last follow‐up. Conclusion: At a median follow‐up of almost 3 years, renal toxicity was uncommon after PT. Longer follow‐up and larger patient cohort data are needed to further assess impact of PT on renal function in this population.